Tinjauan Maqashid Syariah dalam Pengaturan Dispensasi Kawin: Perspektif Perlindungan Hak Anak di Bawah Umur - Nusantara Putri, Kattya (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2024)
This study aims to examine the regulation of marriage dispensation in Indonesian positive law from the perspective of Maqashid Shariah, focusing on the protection of the rights of underage children. Marriage dispensation, which allows underage marriages, raises concerns regarding its negative impacts on the physical, psychological, and social well-being of children. In the context of Maqashid Shariah, the protection of life (hifzh an-nafs), intellect (hifzh al-‘aql), and progeny (hifzh an-nasl) are primary objectives that must be prioritized in any legal policy, including the regulation of marriage dispensation. This research employs a normative juridical method with a qualitative approach to analyze existing legal provisions related to marriage dispensation. This analysis is then linked to Maqashid Shariah to assess whether the policy aligns with the principles of child protection. The findings indicate that the regulation of marriage dispensation in Indonesia, while legally permissible, often neglects child protection aspects in line with Maqashid Shariah’s objectives. This study recommends policy reforms that are more child-centered, ensuring that marriage dispensations are granted only in genuinely urgent situations and that the principles of protection within Maqashid Shariah are fully observed.